N-glycan containing a core α1,3-fucose residue is required for basipetal auxin transport and gravitropic response in rice (Oryza sativa) - Harmoko, Rikno (The New phytologist, 2016)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.